The forest farmers' mindsets contribution to ecosystem degradation in Meru Betiri National Park, Indonesia: towards sustainable conservation through a translation practices approach - Ikhsan, Fahrudi Ahwan; Sumarmi, Sumarmi; Utaya, Sugeng; Sugiarto, Agus; Heldayani, Eni (Brawijaya University, 2026)
Controlling land degradation in conservation areas requires improvement, especially given the spatial impacts of human-environment interactions within the Meru Betiri National Park Biosphere Reserve, Indonesia. Drawing upon geosystem theory, this study investigated land change issues stemming from human-environment interactions within Meru Betiri National Park's conservation area. This study adopted a mixed-methods design that incorporated field observations, surveys, and in-depth interviews. Quantitative data were obtained from observations of the degradation landscape and a survey of forest farmers, while qualitative data were collected through interviews with key observer participants. Data analysis was triangulated through a Forum Group Discussion (FGD) involving forest farmers and policymakers. The findings indicate that forest farmer conservation practices influence knowledge transformation, environmental education, and funding mechanisms. These elements are integral to a sustainable